Pengaruh Persepsi Risiko, Customer Review Serta Jaminan Keamanan Terhadap Minat Pembelian Ulang di Shopee: Studi pada Konsumen Shopee Wilayah Boyolali - Prisella Putri Octaviyani; Wagiyem (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study seeks to analyze the contributions of consumer evaluation, perceived threats and security guarantees on repurchase interest in Shopee on consumers in the Boyolali area. Questionnaires were used in the quantitative methodology of this study to obtain data. The research sample consisted of 97 Shopee Users who have transacted twice per month are also categorized as silver. The sample was selected from purposive sampling. The lesson report will use multiple linear regression. SPSS support media is used to manage the report. From this lesson it is produced that, repurchase interest was not influenced by the risk perception variable, but was significantly influenced by the customer review and security guarantee variables.